2004
DOI: 10.1111/j.1471-0528.2004.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic abscess following microwave endometrial ablation

Abstract: A 44 year old woman presented with severe left-sided lower abdominal pain three days after a microwave endometrial ablation for menorrhagia. The pain was described as sharp, worsened with movement and associated with vomiting. She had not opened bowels since the operation. It was severe enough to require opiate analgesia. She had undergone a microwave endometrial ablation procedure three years previously for treatment of menorrhagia. However, over the last eight months, the symptoms had returned and she reques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
0
8
1
1
Order By: Relevance
“…It is important to consider the safety of MEA, as complications include heat injury to the pelvic organs, uid retention in the uterus (because of cervical stenosis or the ablated endometrium), hematometra, pelvic in ammation (e.g., endometritis because of ascending infection), and pyometra. 9 However, we did not detect any of these complications, which may be related to the use of a resectoscope to evaluate the endometrial lining immediately after MEA. This step allowed for the maximum removal of the necrotic tissue left over by ablation, and we believe that it can improve the safety of MEA by reducing the rate of complications.…”
Section: Discussioncontrasting
confidence: 56%
“…It is important to consider the safety of MEA, as complications include heat injury to the pelvic organs, uid retention in the uterus (because of cervical stenosis or the ablated endometrium), hematometra, pelvic in ammation (e.g., endometritis because of ascending infection), and pyometra. 9 However, we did not detect any of these complications, which may be related to the use of a resectoscope to evaluate the endometrial lining immediately after MEA. This step allowed for the maximum removal of the necrotic tissue left over by ablation, and we believe that it can improve the safety of MEA by reducing the rate of complications.…”
Section: Discussioncontrasting
confidence: 56%
“…Abscesses have been reported after treatment with endometrial ablation however, these have only been reported as presenting within the first few weeks after surgery 79. There is a risk of full thickness uterine damage after endometrial ablation and this may represent another mechanism for the association of appendicitis and uterine abscess in this case as there is the possibility the appendix adhered to the uterus at the time of the ablation procedure.…”
Section: Discussionmentioning
confidence: 83%
“…For the time period January 2003 to December 2006, no hydro or haematosalpinges were reported. There is a solitary report of a pelvic abscess following MEA reported in the literature [17].…”
Section: Discussionmentioning
confidence: 98%